Thermochronological constraints on the Cambrian to recent geological evolution of the Argentina passive continental margin - Kollenz, Sebastian; Glasmacher, Ulrich A. (Tectonophysics, 2017)
Passive continental margins are geo-archives that store information from the interplay of endogenous and exogenous forces related to continental rifting, post-breakup history, and climate changes. The recent South Atlantic passive continental margins (SAPCMs) in Brazil, Namibia, and South Africa are partly high-elevated margins (~2000ma.s.l.), and the recent N-S-trending SAPCM in Argentina and Uruguay is of low elevation. In Argentina, an exception in elevation is arising from the higher topography (>1000ma.s.l.) of the two NW-SE-trending mountain ranges Sierras Septentrionales and Sierras Australes. Precambrian metamorphic and intrusive rocks, and siliciclastic rocks of Ordovician to Permian age represent the geological evolution of both areas. The Sierras Australes have been deformed and metamorphosed (incipient - greenschist) during the Gondwanides Orogeny. The low-temperature thermochronological (LTT) data (<240°C) indicated that the Upper Jurassic to Lower Cretaceous opening of the South Atlantic has not completely thermally reset the surface rocks. The LTT archives apatite and zircon still revealed information on the pre- to post-orogenic history of the Gondwanides and the Mesozoic and Cenozoic South Atlantic geological evolution. Upper Carboniferous zircon (U-Th/He)-ages (ZHe) indicate the earliest cooling below 180°C/1Ma. Most of the ZHe-ages are of Upper Triassic to Jurassic age. The apatite fission-track ages (AFT) of Sierras Septentrionales and the eastern part of Sierras Australes indicate the South Atlantic rifting and, thereafter. AFT-ages of Middle to Upper Triassic on the western side of the Sierras Australes are in contrast, indicating a Triassic exhumation caused by the eastward thrusting along the Sauce Grande wrench. The corresponding t-T models report a complex subsidence and exhumation history with variable rates since the Ordovician. Based on the LTT-data and the numerical modelling we assume that the NW-SE-trending mountain ranges received their geographic NW-SE orientation during the syn- to post-orogenic history of the Gondwanides.
Available online 19 November 2016
Gesehen am 08.11.2018